Performansi Sistem Solid Dry Pad Dengan Media Pendingin 75% Massa Dry Ice - Krisna Yoga, Dwi Wahyu; Wijaksana, Hendra; Suarnadwipa, I Nengah (Teknik Desain Mekanika, 2021)
Abstract Air Conditioner is a very important instrument in the present because it serves to cool the air in a room, Indonesia temperate trofis, with the average temperature reaches 35°C where a comfortable temperature required is 22oC- 26oC. The use of AC earth raises tempratur rate increases, see these problems in need of a cooling machine that is not wasteful of energy and does not damage the environment. Dew Point Evaporative Cooling Namely, this system including the cooling process by contacting the air directly to the cold pad. In a study conducted staggered pad wear berjumlahkan 32 lengths of pipe containing 75% by mass of dry ice, this test is performed to test the performance of Dew Point Evaporative Cooling. With the research variables are variations in air flow rate where V1= 4.8 m/s, V2= 9.5 m/s, V3= 11.3 m/s. Which will dilahkukan measurements including aspects decreasing air dry bulb temperature, capacity, cooling effectiveness, EER and Pressure drop. Results obtained from this research that a decrease in air-dry bulb temperature (?TdB) tends to occur at higher air flow velocity of 4.8 m/s, in getting air temperature difference reduction Tin and Tout as 6,01oC, compared to the air flow rate of 11.3 m/s arising drop in air temperature Tin and Tout of 3,46oC entirely cools and decrease the moisture content in the air. Keywords: Evaporative Cooling, Dew Point, Dry Ice, SDP